Brief Overview and Experience of Visual Evoked Potential of First 67 cases at Referral Neuroscience Hospital in Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2020)
Background: The visual evoked potentials (VEP) is a valuable tool to document occult lesions of the central visual channels especially within the optic nerve.Objectives: The purpose of the present study was to observe the findings of first few cases of VEP done in the neurophysiology department of the National Institute of Neurosciences (NINS), Dhaka, Bangladesh.Methodology: This cross-sectional study was conducted in the Department of Neurophysiology at the National Institute of Neurosciences and Hospital, Dhaka, Bangladesh from September 2017 to March 2020. All patients referred to the Neurophysiology Department of NINS for VEP were included. Pattern reversal VEPs were done using standard protocol set by International Federation of Clinical Neurophysiology (IFCN).Results: The mean age of the study population was 30.70 (±12.11) years (6-68 years) with 31 (46.3%) male and 36 (53.7%) female patients. The mean duration of illness was 8.71 (±1.78) months (3 days- 120 months). Most common presenting symptom was blurring of vision (37.3%) and dimness of vision (32.8%). Patterned VEP revealed mixed type (both demyelinating and axonal) of abnormality in most cases [29(43.35)]. The most common clinical diagnosis was multiple sclerosis (29.85%) and optic neuropathy (26.87%). In the clinically suspected cases of multiple sclerosis, optic neuropathy and optic neuritis most of the cases of VEP were abnormal and the p value is 0.04 in optic neuropathy and optic neuritis.Conclusion: The commonest presentation of the patients in this series were blurring of vision and dimness of vision. The most common clinical diagnosis for which VEP was asked for, was optic neuritis and multiple sclerosis. Most abnormalities were of mixed pattern (demyelinating and axonal).Journal of National Institute of Neurosciences Bangladesh, 2020;6(2): 74-77